2018
DOI: 10.1039/c8dt02960a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nitrite ions in environment analysis with a paper-based microfluidic device

Abstract: A new microfluidic paper-based analytical device, a (Ag-μPAD)-based chemiresistor composed of silver ink, has been developed for the selective, sensitive, and quantitative determination of nitrite ions in environmental analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…There is indeed a concern that most environmental inspection assays could not meet outdoor onsite detection due to the requirements of complicated instruments and a relative long detection time [ 73 ]. With properties of low cost, easy operation, great portability, and easy disposal, paper-based sensors were found reliable to detect carbon dioxide [ 33 ], airborne particulate [ 74 ], volatile organic compounds [ 75 ] in the air, heavy metals [ 76 ], phosphates [ 77 ], inorganic element ions [ 78 , 79 , 80 ], nitrite [ 81 ], and nicotine [ 82 ] in the water.…”
Section: Paper-based Sensors For Environmental Quality Inspectionmentioning
confidence: 99%
“…There is indeed a concern that most environmental inspection assays could not meet outdoor onsite detection due to the requirements of complicated instruments and a relative long detection time [ 73 ]. With properties of low cost, easy operation, great portability, and easy disposal, paper-based sensors were found reliable to detect carbon dioxide [ 33 ], airborne particulate [ 74 ], volatile organic compounds [ 75 ] in the air, heavy metals [ 76 ], phosphates [ 77 ], inorganic element ions [ 78 , 79 , 80 ], nitrite [ 81 ], and nicotine [ 82 ] in the water.…”
Section: Paper-based Sensors For Environmental Quality Inspectionmentioning
confidence: 99%
“…35 Details of the synthesis procedure of AgNPs have been previously described elsewhere. 26 At rst, NaCl (30 mM) was added to 30.2 mL EG solution of AgNO 3 (50 mM) and PVP (280 mM) at a ow rate 1.0 mL min À1 . Then, the mixture was reuxed at 130 C for 30 min.…”
Section: Le-pads Fabricationmentioning
confidence: 99%
“…25 In our previous work, a microuidic paperbased device developed by chemiresistive method was used for quantitative detection of nitrite with a low detection limit. 26 Since UTIs are common, especially in persons with indwelling urinary catheters, clinically-effective and costeffective tests for diagnosis and investigation are needed. 4 Regarding the urine dipstick assay, the Kuppusamy group found that the reliability of UTI diagnosis was highest when nitrite, leukocyte and blood were considered together.…”
Section: Introductionmentioning
confidence: 99%
“…The potassium cation (K + ) is one of the most abundant physi ological metal ions in living organisms, playing vital roles in many biological processes, such as blood pressure control, to afford their practical application in our daily lives as pointofcare (POC) sensors. Chemiresistors (CRs) [11] are a compelling alternative which possess considerable advan tages for POC applications, including excellent sensitivity, costeffectiveness, simple sensing mechanism, [12] port ability, [13] facile integration into microfluidic systems, [14] and combination with optoelectronic transducers. [15] Noble metal nanoparticles (NPs) are ideal scaffolds for the fabrication of different types of sensing devices, [16] especially CRs, [12,17] due to their high surfacetovolume ratio and unique optical and electrical properties, which are very sensitive to chemical events occurring in their surroundings.…”
Section: Introductionmentioning
confidence: 99%